(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
„Do Not Kill”: Violation of the Prohibition / Commandment and Its Consequences (Reflections on the Novel „Drama of the House of Timoteu” by Mircea Streinul) The article proposes a conceptual retrospective of the term shadow in psychoanalysis, defining the fable of the novel that follows the biblical prescription of the supreme sin of «don’t kill» and the conflicting experiences of the characters. In this article we explore the tellurium imaginary in the novel Drama of the house of Timoteu by Mircea Streinu, the multifaceted evil, the diabolical characteristics of the characters and the description of nature in negative terms. By emphasizing “do not kill” we try to prove that killing is the most abominable fact, which demonstrates man’s lack of humanity.